Aprendizaje-Servicio como instrumento para la accesibilidad y la inclusión: resultado de una propuesta colaborativa entre universidades y bibliotecas (Service-learning as a tool for accessibility and inclusion: results of a collaborative approach between - Elena Loreto Olmedo-Pagés; Rosario Arquero-Avilés (Information Research: An International Electronic Journal)
Introduction. Teaching innovation projects based on service-learning (SL) have proven to be beneficial in the creation of alliances between organisations committed to pooling their efforts and resources to have a positive impact on their environment.